Effect of near-fault vertical seismic excitation on the response of long-span continuous deck truss bridges - Benmahdi, Khaled; Lahbari, Noureddine; Rahal, Nacer; Demdoum, Abdellah; Sadoun, Mohamed; Beghdad, Houda (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: This study investigates the seismic response of long-span continuous deck truss bridges under the effect of near-fault vertical ground motions. The primary objective is to assess how near-fault vertical seismic excitation affects the structural safety and performance of these bridges. By exploring the nuanced dynamics induced by near-fault vertical motions, the research aims to improve the understanding of the vulnerabilities and challenges faced by long-span continuous deck truss bridges during seismic events. Methods: To achieve this objective, the truss bridge was subjected to a series of ground motions, representing natural seismic events. The seismic response of the bridge was investigated by applying the linear time history method to the 3D finite element model. This analysis focused specifically on the evaluation of base shear and displacement. The analysis was extended to include the seismic performance of truss structures. The comparison between the bridge responses with and without consideration of the vertical component of ground motion was made to clarify the effect of vertical excitation. Results: The results show that there is a significant contribution of vertical excitation, particularly concerning the internal force in the truss elements, where it exceeded 60 % during a severe earthquake, and consequently increased the demand-to-capacity ratio in most elements of the truss bridge structure. Conclusion: For structural engineers and designers, the results of this research suggest that neglecting to include the vertical ground motion component in the analytical assessments of this type of bridges can lead to a greater degree of uncertainty and risk, particularly in near-fault regions.